Airbus : Brexit and the trans-European business catalyst - Suder, Gabriele (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Airbus is one of the most well-known inherently cross-European examples of business ventures that make significant use of market integration and the diversity of the European marketplace. This unique European Aeronautic Defence and Space company case on AIRBUS symbolises the opportunity for business success at home and abroad when firms evolve simultaneously with regional integration. Many argue the European aerospace corporation's success to be deeply embedded in a most extraordinary multi-country economic integration that its makers are part of: Airbus - founded in 1970 as a consortium of various European aviation firms - was seen as a function and, to some extent, a catalyst of the resulting business environment. The European Union has widened and deepened in its harmonisation and regulatory convergence efforts for the benefit of economic, social and geopolitical collaboration. Yet Brexit, the UK's exit from the European Union in early 2019, opens up a number of questions: How can Airbus survive mounting challenges, including cyclically widening and narrowing integration, and a unique dependence on suppliers, in its current set-up and organisation that is based on the European Union's enhanced market integration? How could contemporary trends in regionalisation cause a company like Airbus to adjust its current structure and its regional and global value chains?
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Airbus (Firm); European Union -- Great Britain; Industrial management -- Europe; International business enterprises -- Europe